Model Pengembangan Usaha Produk Bayi dan Anak Halomam Berbasis Pendekatan Business Model Canvas - Sucayono Sucayono (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study addresses the lack of integration in the business model of Halomam, a retail business specializing in baby and children’s products, which limits its marketing effectiveness and revenue diversification. The objective of this research is to analyze the existing business model and propose its development using the Business Model Canvas (BMC) approach. A qualitative descriptive method was employed, with data collected through in-depth interviews, direct observation, and documentation involving key informants, including the business owner and staff. The analysis followed a systematic process of data condensation, data display, and conclusion drawing. The findings reveal that Halomam’s business model is not yet fully integrated, particularly in customer segmentation, which remains broad and insufficiently targeted. In addition, revenue streams rely primarily on product sales without significant diversification. However, the business demonstrates considerable potential in its key resources, activities, and partnerships. This study contributes by offering a structured evaluation of a small retail business model and proposing strategic directions, including more specific customer segmentation, strengthened digital marketing, and diversified revenue streams to enhance competitiveness and long-term sustainability.